PEMBUATAN ACARA LIVE STREAMING “JOOX LIVE NOW” SEBAGAI BENTUK KONTEN RADIO DI ERA DIGITAL - Chalvin Sharon Mongkol; Aditya Nugroho Pratomo; Dhita Widya Putri (LPPM UNIVERSITAS DIAN NUSWANTORO, 2019)
The development of technology and communication has brought many changes, especially in broadcast industry. Since the internet era, people could listen to music through various media portals that they accessed through smartphones. This trend is known as media convergence, where there is an interlacing between internet and radio. The birth of media convergence in radio industry also gave rise to the term of ‘streaming’, where the content broadcasted live through the internet, in the form of audio and video. One of the streaming radio service providers in Indonesia is JOOX. This scientific work’s aim is to provide an overview and contribution to the era of new media, especially for music and radio industry. The concept of online strategy in music radio programming from Newton and Kaiser is being used. The result showed that JOOX is an audio visual based live streaming program that facilitates musicians to promote their new albums, as well as the place to interact with their fans through the live-chat feature as a form of engagement.